THE INFLUENCE OF LEADERSHIP COMMUNICATION PATTERNS ON THE PERFORMANCE OF EMPLOYEES OF EAST LUWU DISTRICT HUMAN RESOURCES AND HUMAN RESOURCES (Karya Ilmiah Mahasiswa (KIMA), 2024)
The purpose of this study aims to: determine the influence of leadership communication patterns on employee performance on the quality of work of East Luwu BKPSDM employees. The study lasted for approximately one month from May 2023 to June 2023. Located at the Office of the East Luwu Human Resources Personnel and Development Agency (BKPSDM) with a population of 35 people. The method used in this study is a quantitative method of descriptive statistics analysis with a data collection process using surveys in the form of questionnaires, data analysis using linear regression analysis. While the theories used in this study are leadership theory and SOR (Stimulus-Organism-Response) Theory. The results of statistical research that have been carried out previously variable Individual Characteristics have a calculated value of 7.834 ≥ table 2, 034 and the significance value is 0.000 ≤ 0.05, then the Leader's Communication Style partially has a significant positive effect on Employee Performance. This means that the leader's communication to his employees is very significant, if the leader has a good communication relationship with his subordinates then this will support the improvement of performance by employees.